Psychological birth trauma and its related factors, and providing strategies for prevention of psychological birth trauma: protocol for an explanatory sequential mixed-method study - Mojgan Mirghafourvand; Alireza Shafiee-kandjani; Sakineh Mohammad-Alizadeh-Charandabi; Mahnaz Shahnazi; Fatemeh Abbasalizadeh; Minoo Ranjbar (BMJ Open, 2025)
Background Childbirth can have psychological, social and emotional effects on women and their families. Psychological birth trauma (PBT) is defined as the emotional distress and mental health challenges resulting from negative or distressing experiences during the childbirth process. Labour management plays an important role in the health of women and children. Consequently, the study aims to assess the status of PBT among Iranian women, identify factors influencing it and suggest effective preventive strategies.Methods and analysis This study is a mixed-method research with an explanatory sequential approach. The first phase is quantitative and cross-sectional, involving 300 postpartum women visiting health centres in Tabriz-Iran. In this phase, cluster sampling will be used, and data will be collected using the following questionnaires: Sociodemographic and Obstetric Characteristics, Birth Trauma Scale, PTSD Symptom Scale 1, Perceived Quality of Care Scale, Childbirth Experience Questionnaire version 2.0, Edinburgh Postpartum Depression Scale, Postpartum Specific Anxiety Scale Research Short-Form and the questionnaire on the desire for subsequent pregnancy. The second phase is qualitative, and participants will be selected based on the results of the quantitative phase and extreme cases, using purposive sampling. Data analysis will be performed using qualitative content analysis with a conventional approach. Qualitative data will be collected through in-depth and semi-structured individual interviews with open-ended questions. In the third phase, strategies to prevent childbirth psychological trauma will be designed by integrating the results of the quantitative and qualitative studies, reviewing the literature and gathering expert opinions using a modified Delphi study. Examining PBT and its influencing factors can provide culturally relevant, evidence-based strategies. These strategies can be effective in improving the quality of care for women during childbirth.Ethics and dissemination This study has received approval from the Ethics Committee of Tabriz University of Medical Sciences in Tabriz, Iran (code number: IR.TBZMED.REC.1402.945). All participants will provide written informed consent before taking part in the study. The outcomes will be shared through articles published in journals, presentations at medical conferences, the validation of a reliable scale for assessing the level of PBT in postpartum women, and the provision of strategies to prevent childbirth psychological trauma. These resources will be valuable for policymakers and healthcare providers.